An Analysis of Relationship Between Remittance and Inflation in Nepal: An Empirical Study - Dahal, Ananta Raj (Cognition, 2021)
Remittance is the importance sources of income generation in the Nepal. It play vital role of the Nepalese national income as well as precipitate income. The study has analysis the role of the remittance to increase the inflation of the country. The main objective of the paper is to analysis the relationship between remittances and inflation in Nepal. In this research only secondary data were used from the different sources. The infernal statistics were used the data analysis like regression and correlation. By the applying of the regression model in difference variable result are not same. After the model fit explanatory variables like remittance, broad money supply and government expenditure has significant. The regression results suggest that that the remittances are positively associated with inflation. Like same the correlation coefficient between remittance and inflation is 0.6419. This is statistically significant at 5% level and moderate positive correlation, which means there is a tendency for high inflation with high remittance inflow.